2016
DOI: 10.1111/acem.12867
|View full text |Cite
|
Sign up to set email alerts
|

Handoff Practices in Emergency Medicine: Are We Making Progress?

Abstract: Objectives: Transitions of care present a risk for communication error and may adversely affect patient care. This study addresses the scope of current handoff practices amongst U.S. emergency medicine (EM) residents. In addition, it evaluates current educational and evaluation practices related to handoffs. Given the ever-increasing emphasis on transitions of care in medicine, we sought to determine if interval changes in resident transition of care education, assessment, and proficiency have occurred.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…6 7 8 The CORD survey showed that over half of the respondents from academic EDs indicated that their EDs use a standardized handoff. 9 However, it is not known how emergency medicine (EM) residency programs are providing training around care transitions from the ED to inpatient settings.…”
Section: Introductionmentioning
confidence: 99%
“…6 7 8 The CORD survey showed that over half of the respondents from academic EDs indicated that their EDs use a standardized handoff. 9 However, it is not known how emergency medicine (EM) residency programs are providing training around care transitions from the ED to inpatient settings.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Hern et al, 57% of residency programs had curriculum focused on transitions of care. Hern et al recently found 57% of residency programs have curriculum focused on handoffs, a much higher percentage than PE 12. Another study found 93% of residency programs had curriculum focused on operations and administration.…”
Section: Discussionmentioning
confidence: 99%
“…Communication miscues and omissions, the most frequently numerated barrier to efective patient transition of care [17], correspond with the lack of consensus about the elements of efective handof [2]. Substantial variability exists across, and sometimes within, institutions regarding preferred formats and processes for verbal and writen handofs.…”
Section: Barriers To Efective Handofsmentioning
confidence: 99%
“…Substantial variability exists across, and sometimes within, institutions regarding preferred formats and processes for verbal and writen handofs. Research of residency training programs nationally indicate that handof standardization has not been aggressively implemented and evaluated among residency training programs or implemented with variable compliance [2,18].…”
Section: Barriers To Efective Handofsmentioning
confidence: 99%
See 1 more Smart Citation